Peran KUD Mina “Samudra Jaya” Terhadap Budaya Simpan Pinjam (Uang Beranak) Di Wilayah Pesisir Panarukan Situbondo - Suryadinata, Ningrum; Aprillia, Jesika Wanda (Indonesian Accounting Literacy Journal, 2025)
Mina "Samudra Jaya" is a cooperative that employs fishermen as its members. This study aims to evaluate cooperatives' financial condition with financial assessments of health and examine how it contribute to loan and savings activities that influence the development of the culture. The analysis is qualitative-descriptive, it uses financial statements from 2018-2019 as secondary data. Cooperative is the subject, and the seven components of cooperative financial assessment are the object. The quality of productive assets, capitalization, management, efficiency, liquidity, and ROE, the cooperative's identity are among the criteria evaluated in this study. The methods and instruments for data collection included triangulation, documentation of fishermen's activities, interviews, and observation. The result, the cooperative's financial health is being monitored in seven items. The ratios of members' operating expenses to gross participation, loans to funds received, and economic promotion were 81.41%, 89.23%, and 89.92%, respectively, in the healthy group.